2016
DOI: 10.1007/s11422-016-9742-8
|View full text |Cite
|
Sign up to set email alerts
|

“Shut up and calculate”: the available discursive positions in quantum physics courses

Abstract: Educating new generations of physicists is often seen as a matter of attracting good students, teaching them physics and making sure that they stay at the university. Sometimes, questions are also raised about what could be done to increase diversity in recruitment. Using a discursive perspective, in this study of three introductory quantum physics courses at two Swedish universities, we instead ask what it means to become a physicist, and whether certain ways of becoming a physicist and doing physics is privi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 29 publications
2
55
1
15
Order By: Relevance
“…In the second study, I and my co-authors take a similar discursive approach to undergraduate quantum physics [6]. In this ethnographically inspired study of three courses in quantum physics at Swedish universities, we found that many different views of what quantum physics is about were expressed in the discourse of courses, teachers and students.…”
Section: Insights From Employing a Discursive View Of Identitymentioning
confidence: 92%
See 1 more Smart Citation
“…In the second study, I and my co-authors take a similar discursive approach to undergraduate quantum physics [6]. In this ethnographically inspired study of three courses in quantum physics at Swedish universities, we found that many different views of what quantum physics is about were expressed in the discourse of courses, teachers and students.…”
Section: Insights From Employing a Discursive View Of Identitymentioning
confidence: 92%
“…In particular, I will discuss the poststructuralist notion of discourse as a social structure for interpretation that shapes what can be said, done or understood in a certain context. Drawing on two studies from my PhD-project [5,6] and other studies of identity in physics education [4,[7][8][9][10], I will argue that using a discursive perspective of identity enables us to answer important questions about students' various relationships to physics without taking the norms of the discipline for granted. For example, in the projects reported here, I and my co-authors have seen how students' negotiations of learning practice in an electromagnetism course can be affected by cultural norms around physics and how the teaching and learning practice in quantum physics classrooms can limit the ways of identifying as a physicist for students.…”
Section: Introductionmentioning
confidence: 99%
“…Our research could also encourage teachers to address different QP interpretations in their lessons because many interviewees mentioned that the idea of the 'unsolved problem' of QP makes the subject more attractive than the 'facts' physicists agreed on long ago. By including philosophical aspects in QP lessons, teachers could not only broaden students' views on the subject but also involve and attract a larger variety of students (Johansson et al, 2018).…”
Section: Implications For Educationmentioning
confidence: 99%
“…While forming a physicist demands for him to learn to substitute values in equations whose meaning, construction, and implications mean anything to him (an issue that must be addressed) (Johansson, Andersson, Salminen-Karlsson, & Elmgren, 2016), forming a citizen takes much more than that. We cannot simply copy the baccalaureate model for high school simply by deleting the derivatives and integrals.…”
Section: Final Considerationsmentioning
confidence: 99%